UML by example - Jalloul, Ghinwa (Cambridge University Press, 2004)
Ghinwa Jalloul's step-by-step introduction to object-oriented software development is suitable for teacher training as well as for practicing software engineers. Jalloul presents seven complete case studies and several smaller examples documented in UML, derived from small software projects developed for, and delivered to, real users. They are preceded by an overview of the object-oriented modeling artifacts in UML, on which the remainder of the book relies. The case studies provide a medium for experimental use and act as templates that can be tailored by readers to fit specific needs and circumstances.